Gimnasia cerebral y atención en niños de preparatoria de la Escuela de Educación Básica Fiscal Filomena Mora de Carrión de la ciudad de Loja, periodo 2023-2024. - Jaén Armijos, Carolina Maribel (2024)
Attention is the cognitive process that allows concentration on specific stimuli from the environment while ignoring others, facilitating more efficient processing of information and thereby improving learning. Therefore, the purpose of this research was to analyze the contribution of brain gym exercises to improve attention in 5 to 6 years old children. The study was conducted with a mixed approach, descriptive scope, and non-experimental design. The inductive-deductive and analytical-synthetic methods were essential in gathering relevant bibliographic information for the research. The observation technique provided direct information about the object of study. The detection and evaluation instrument for attention and memory learning difficulties, developed by the Ministry of Education of Bolivia and applied to a sample of twenty-four preschool children, revealed that 83% had mild and moderate attention problems; while 17% had a severe attention problem, these children showed difficulties in completing tasks, following specific instructions, discriminating figures, focusing attention on a particular stimulus, identifying elements, and assimilating new concepts. To address this issue, an alternative proposal based on brain gym exercises called "Mind in Motion" was implemented, including thirty activities designed to address different types of attention (selective, focused, divided, sustained). According to bibliographic information, brain gym exercises stimulate cognitive development by strengthening neural connections, improving concentration and memory. Additionally, they promote healthy learning habits and contribute to holistic development, enabling children to better face educational and social challenges from an early age. Keywords: attention, coordination, exercises, cognitive functions, brain hemispheres.